Serious road injuries in The Netherlands dissected. (2nd January 2016) - Weijermars, Wendy; Bos, Niels; Stipdonk, Henk L.
ABSTRACT: Objective: This article discusses the characteristics and injury patterns of serious road injuries (Maximum Abbreviated Injury Scale [MAIS] 2+ inpatients) in The Netherlands. Methods: In The Netherlands, the actual number of serious injuries is estimated by linking police data to hospital data. The distribution of serious road injuries over (1) travel mode and gender and (2) crash type and age are compared for the years 2000 and 2011. Moreover, the distribution of the injuries over the body regions is illustrated using colored injury body profiles. Results: The number of serious injuries is higher for men than for women and increased from 16, 500 in 2000 to 19, 700 in 2011. In 2011, about half (51%) of the serious road injuries were due to a bicycle crash not involving a motor vehicle. The share of casualties aged 60 years and older is relatively high (43% in 2011) in these crashes. The injury body profiles show that head injuries (31%) and injuries to the lower extremities (37%) are most prevalent. Compared to other travel modes, pedestrians and riders of powered 2-wheelers relatively often sustain lower-leg injuries compared to other travel modes. Head injuries are most prevalent in cyclists who are injured in a crash with a motorized vehicle. Cyclists who are injured in a crash not involving a motor vehicle and casualties of 60 years and older relatively often include hip or upper-leg injuries. Conclusion: The characteristics of serious road injuries differ from those of fatalities and the distribution of injuries over the body differs by travel mode, gender, and age.